HUBUNGAN INTERAKSI SOSIAL SISWA TERHADAP KEMAMPUAN BERNALAR KRITIS PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD - Selvia Karmelita; Sri Wahyuningsih; Mega Prasrihamni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to find out whether there is a relationship between students' social interaction and critical reasoning skills in Indonesian Lessons Class IV SD Negeri 10 Muntok. The method used in this study is quantitative research, which is divided into two types, namely, Independent variables, also known as independent variables, refer to a factor that has the potential to affect other variables in a study and Bound variables, or also called dependent variables. Based on the results of the social interaction questionnaire data, it is known that the maximum score obtained is 94 and the minimum is 66. Based on the data on the results of the critical reasoning test for students in grades IV A and IV B which amounted to From the table data of 46 students, it can be seen that the maximum score is 100 and the minimum score is 60. From the results of the normality analysis The social interaction questionnaire obtained a significance value of 0.163 and in critical reasoning was 0.065. Based on the results of the analysis and discussion, it can be concluded that there is a relationship between students' social interaction and critical reasoning skills in the Indonesian subject in grade IV elementary school which in the hypothesis test there is a strong relationship.